Interaktionsschemata als Ordnungsprinzip von Textkorpora gesprochener Sprache - Prokop, Izabela (Studia Germanica Posnaniensia, 2018)
The article is a methodical contribution to the analysis of spoken language. In its first part the author points to the difficulties in the classification of spoken language records. She then describes the various stages of analysis with the aim of obtaining homogeneous text corpora. lnteraction patterns characteristic of two communication situations (in a shop and in an office) are presented. The author recommends such patterns for all types of interaction.